PENERAPAN PRINSIP ANALISA 5C DALAM PERJANJIAN KREDIT (PUTUSAN NOMOR 90/PDT.G/2021/PN PLG): Application Of 5c Analysis Principles In Credit Agreement (Decision Number 90/Pdt.G/2021/Pn Palembang) - Edgar Joseph; Dinda Keumala (Faculty of Law, Universitas Trisakti, 2025)
PT. Bank Perkreditan Rakyat Puskopat Palembang entered into a credit agreement with a debtor without optimally applying the 5C analysis principle as mandated by banking regulations. This gives rise to legal issues, particularly regarding negligence in collateral procedures and violations of regulations on the registration of security rights. The issues examined in this study are: how is the application of the 5C analysis principle in the credit agreement between PT. BPR Puskopat Palembang and the debtor based on Decision Number 90/Pdt.G/2021/PN Plg? and what are the legal consequences of failing to apply the 5C analysis principle in the said credit agreement? The legal research method employed is normative juridical research with a descriptive approach. It is concluded that there is no implementation of the 5C analysis principle in accordance with banking regulations, particularly in the matter of collateral, due to the absence of an adequate standard operating procedure for credit agreements. Furthermore, the registration of security rights by the PPAT was carried out in violation of prevailing regulations, resulting in substantial material losses for the bank.